Simultaneous transverse loading and axial strain for REBCO cable tests in the SULTAN facility. (1st July 2022) - Fry, Vincent; Estrada, Jose; Michael, Philip C; Salazar, Erica E; Vieira, Rui F; Hartwig, Zachary S
Abstract: We present the design and first results of an assembly that enables rare earth barium copper oxide (REBCO) superconducting cables—the VIPER cable in this work—to be tested in the SULTAN facility under the simultaneous application of transverse electromechanical loading and axial mechanical strain. The objective is to emulate the loads that a REBCO cable would experience in a three-dimensional coil but in shorter and simpler straight cables, reducing the cost, schedule, and complexity of high-fidelity conductor qualification. The assembly uses two methods for inducing axial strain in the cables. First, hydraulic jacks stretch the assembly and inserted Invar shims lock in up to ∼0.3% axial cable strain on the benchtop at room temperature. Second, the different coefficients of thermal expansion between Invar clamps and the copper cable are exploited to induce an additional ∼0.3% axial strain on the cable when the sample is cooled in the SULTAN test well from room temperature to below 50 K. Finite element analysis modeling shows that the soldered matrix of the VIPER cable transfers approximately 50%–60% of the external cable strain into the REBCO stack. The assembly was successfully employed at SULTAN, enabling two VIPER cables to be cycled 500 times at 382 kN m −1 transverse electromechanical loads with ∼0.5% mechanical strain on the cable (corresponding to ∼0.3% mechanical strain in the REBCO stacks) demonstrating critical current degradation stabilizing after 30 cycles at less than 5% and providing confidence in VIPER cables under realistic high-field magnet conditions.